Position and Authority of the Constitutional Court in the Constitutional System of the Republic of Indonesia - Zainal Abidin (JUSTICES: Journal of Law, 2023)
The Constitutional Court is the only institution with the same position as the Supreme Court, which means that these two courts are the two highest institutions in the judiciary. The Supreme Court is influenced by the Constitutional Court's status as an independent state institution in the judicial sector. Previously, the Supreme Court, which supervised other courts, was the highest institution, but after the establishment of the Constitutional Court, justice was organized by the judiciary. Even with the existence of the Constitutional Court, the power of the Supreme Court in terms of judicial review of laws and regulations can be liberalized by law because its power violates the constitutionality of the law.